2016
DOI: 10.5897/ajb2015.15051
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological properties of cashew (Anacardium occidentale)

Abstract: Anacardium occidentale L. is a tree native to Brazil, which is rich in phenolic lipids. Nowadays, the cashew bark (Cashew Nut Shell Liquid) has received great attention in the pharmaceutical industry, due to its economy, abundance and important chemical compounds. Net of cashew nut shell is classified according to the method of production of: (1) net of the shell of natural cashew nut (60-65% anacardic acid; 15-20% cardol and 10% of cardanol) and (2) liquid from the technical cashew nut shell (60-65% of cardan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 102 publications
0
15
0
1
Order By: Relevance
“…Almost all the chemical elements detected by Zuharah et al (2021) were also observed in the extract of this plant. Recently, the work of Aracelli de Sousa (Aracelli et al, 2016) conducted in Brazil, also revealed that A. occidentale contained high proportions of phenolic compounds. Beyond the phytochemicals detected, the analyses performed showed that the extract of A. occidentale presented the strongest capacities with respect to antioxidant activity, inhibition of anti-acetylcholinesterase, anti-butyrylcholinesterase and tyrosinase.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all the chemical elements detected by Zuharah et al (2021) were also observed in the extract of this plant. Recently, the work of Aracelli de Sousa (Aracelli et al, 2016) conducted in Brazil, also revealed that A. occidentale contained high proportions of phenolic compounds. Beyond the phytochemicals detected, the analyses performed showed that the extract of A. occidentale presented the strongest capacities with respect to antioxidant activity, inhibition of anti-acetylcholinesterase, anti-butyrylcholinesterase and tyrosinase.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study by Abdullah Thaidi et al [1] had reported a positive inhibition effect on α-amylase and DPP-4 enzymes by using the crude extract of A. occidentale shoots, and had been analysed using high performance liquid chromatography (HPLC) to contain phenolic acids and flavonoids compounds which were gallic acid, ferulic acid, quercetin, kaempferol and p-coumaric acid. Besides, other studies had also mentioned the presence of polyphenol compounds in the A. occidentale which are caffeic acid, salicylic acid, sinapic acid, catechin, genistein, robustaflavone, myricetin, apigenin, vanillic acid and protocatechuic acid [1,4,[8][9][25][26][27]. Thus, a total of 15 polyphenols from A. occidentale namely caffeic acid, salicylic acid, sinapic acid, catechin, genistein, robustaflavone, kaemferol, quercetin, myricetin, apigenin, vanillic acid, gallic acid, ferulic acid, protocatechuic acid and ρ-coumaric acid were selected to conduct this current study and predict for future reference.…”
Section: Ligand Preparationmentioning
confidence: 99%
“…Many scholars reviewed the health benefits of cashew and reported that almost all parts of the plant and their constituent are used as a curative against various human diseases such as a toothache, ringworm, coughs, colds, syphilis, stomach-ache, fever, cholera, kidney troubles, diarrhea, asthma, leprosy, elephantiasis, psoriasis, warts, corns fresh wounds and cuts (Aracelli et al, 2016;Judge and Azam-Ali, 2001;Runjala and Kella, 2017). Anacardic acids supplementation has a potential protective role on oxidative and inflammatory mechanisms in the lungs (Carvalho et al, 2013).…”
Section: Health Benefitsmentioning
confidence: 99%